Low-Quality Leadership in a Vertically Differentiated Duopoly with Cournot Competition - Luca Lambertini; Alessandro Tampieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
We model a vertically differentiated duopoly with quantity-setting firms as an extended game in which firms noncooperatively choose the timing of moves at the quality stage, to show that at the subgame perfect equilibrium sequential play obtains, with the low-quality firm taking the leaders role.
Keywords: C73; L13; 330